POVERTY ALLEVIATION IN SPECIAL AUTONOMY SYSTEMS: DYNAMICS AND CHALLENGES OF ASYMMETRIC DECENTRALIZATION - Zulaika, Siti; Fauzi, Fadhli Zul; Suryapuspita, Merintha (Fakultas Politik Pemerintahan IPDN, 2024)
Abstract This study compares the implementation of asymmetric decentralization in Indonesia and its effect on poverty alleviation. The method used in this study is a comparative case study (CCS), where the researchers compare two regions that implement an asymmetrical decentralization system: the Special Region of Yogyakarta and Papua, with different outcomes. From the data collected in the field, researchers found various challenges in implementing asymmetric decentralization, especially in poverty alleviation efforts. In the case of Papua, there are several challenges, including the effective allocation of budget and the strengthening of human resources. In contrast, in Yogyakarta, the focus of implementing legal asymmetry is enhancing culture and governance. Hence, poverty alleviation initiatives must also consider these central aspects. This research can contribute to developing development studies and public policies on poverty alleviation. The researcher provides an in-depth analysis of two exceptional cases applying asymmetrical decentralization in their activities. Keywords: Poverty Alleviation, asymmetric decentralization, comparative case study